The association between physical stature and myopia in elementary and junior high school graduates in Chongqing, China - Zhang, Jing; Li, Ruili; Zhang, Yong; Tang, Wensheng; Ao, Dan; He, Li; Yang, Kun; Qi, Xiaoya; Zhou, Xiyuan (Frontiers in Medicine, 2025)
PurposeThis study aims to investigate the relationship between myopia and physical statures in elementary and junior high school graduates.MethodsEight hundred and seventy-one elementary graduates and 752 junior high graduates in the urban area of Chongqing in China were recruited when they came to the hospital for their physical examination at enrollment. All the participants underwent anthropometric measurements, ocular examination, including visual acuity, slit lamp, non-cycloplegic refraction, and a questionnaire survey on demographics and life habits related to eye use. Univariate and Multivariate regression was used to analyze the relationships between physiques and SER (spherical equivalent refraction).ResultsThe mean ages were 12 ± 0.5 years and 15 ± 0.5 years for graduates in elementary school and in junior high school, respectively, the number of myopic children were 73.8% (643/871) and 82.6% (621/752) in elementary school and in junior high school, respectively. The regression coefficients between SER and height for elementary school graduates were significant in the right eye (B = −0.002, p = 0.011) and in the left eye (B = −0.025, p = 0.005) by univariate analysis. These negative associations between SER and height in elementary graduates were significant after adjusting for multiple covariates (B = −0.020, p = 0.025 for right eye and B = −0.022, p = 0.014 for left eye). On the contrary, physical indexes were not significantly related to SER in junior high school graduates in univariate analysis and multivariate analysis.ConclusionAccelerated height growth at elementary school may increase the risk of myopia by accelerating the process of emmetropization, but this relationship may be covered up by other risk factors, especially the increased near-sight activity due to increased academic work at higher grades. Further study is warranted to explore this relationship in children of different ages.